PENGARUH DIGITAL MARKETING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA TOKOPEDIA DI KOTA PALEMBANG - Naruliza, Esty; Suseno, Rico (Fakultas Ekonomi Universitas IBA, 2021)
Along with the development of the era, which is supported by the development of increasingly sophisticated technology, it has an impact on increasingly fierce business competition. Various efforts have been made by the company in order to have a strong traction stuck in the minds of consumers. The strategy used to introduce a brand is to use digital marketing. The higher the level of brand awareness (brand awareness), the more inherent a brand will be in the minds of consumers, so the more likely the brand will be chosen by consumers. In this study, the object is Tokopedia's consumers in the city of Palembang. The sampling method uses accidental sampling. The data used are primary data by distributing questionnaires directly to Tokopedia application users in the city of Palembang. The number of samples used was 272 respondents. The test was carried out in three stages, namely validity, reliability, classical assumption and hypothesis testing. The results of this study indicate that digital marketing and brand awareness together have a positive effect on purchasing decisions of Tokopedia consumers in Palembang, this can be seen from the results of the multiple regression test Y = 18,950 + 0.556 X1 + 0.28 X2 + e. When viewed from the coefficient of determination (R2) of 34.9%, purchasing decisions can be explained by digital marketing and brand awareness. Meanwhile, 65.1% was influenced by other variables not examined in this study, such as discounts, hsrgs, availability of goods and others.